2004
DOI: 10.1002/biof.5520220164
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional analysis of Vietnamese seaweeds for food and medicine

Abstract: Vietnamese edible marine macro-algae (seaweed) are of interest because of their value in nutrition and medicine. Vietnamese living in the coastal have traditionally utilized seaweeds species as food supplement and herbal medicine. They consumed seaweed as food in various forms: raw as salad and vegetable, pickle with sauce or with vinegar, relish or sweetened jellies and also cooked for vegetable soup. As herbal medicine, seaweed is usually used for traditional comestics, treatments for cough, asthma, hemorrho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 1 publication
3
18
0
2
Order By: Relevance
“…6 The high concentration of calcium (5.24 g kg −1 ) can be attributed to the greater accumulation of this than in terrestrial foodstuffs. 17 These results are similar to those obtained by Carrillo et al, 18 MacArtain et al 17 and Mabeau and Fleurence, 1 and are within the range reported by the same authors and by Hong and Hien 4 and Ruperez 19 for other algae. Seaweeds have been described as a good source of iodine, which is important in metabolic regulation and growth, although consumption of very large amounts may induce some negative toxic effects.…”
Section: Resultssupporting
confidence: 95%
See 1 more Smart Citation
“…6 The high concentration of calcium (5.24 g kg −1 ) can be attributed to the greater accumulation of this than in terrestrial foodstuffs. 17 These results are similar to those obtained by Carrillo et al, 18 MacArtain et al 17 and Mabeau and Fleurence, 1 and are within the range reported by the same authors and by Hong and Hien 4 and Ruperez 19 for other algae. Seaweeds have been described as a good source of iodine, which is important in metabolic regulation and growth, although consumption of very large amounts may induce some negative toxic effects.…”
Section: Resultssupporting
confidence: 95%
“…1 -3 Some of the major economically important seaweed groups can be used for human and animal consumption. 4 In general, seaweeds are rich in polysaccharides, vitamins and minerals, low in fat and have a high protein content. However, data on the bioavailability of these components are limited.…”
Section: Introductionmentioning
confidence: 99%
“…The values obtained in the carbohydrate investigation for the three algae are above the contents reported by several authors for fruits and vegetables daily consumed; they only resemble the carbohydrate content in dried fruit [32]. The high carbohydrate content is a very marked characteristic in most algae, comprising mainly soluble carbohydrates, sugars, including pectins, plus a lot of alginic acid in M. pyrifera and agar and carrageenan in G. chilensis [40][41][42].…”
Section: Carbohydratesmentioning
confidence: 82%
“…The content of microelements in Gracilaria such as Fe, Mn, Zn, Co, Pb, and Mo were analyzed through the use of atomic absorption spectrometry. The content of I and B were analyzed by the color comparison method using UV-VIS, UV-160IPC (Shimadzu, Japan) (Hong and Hien 2004).…”
Section: Methodsmentioning
confidence: 99%